Pulmonary retention of free and liposome-encapsulated tobramycin after intratracheal administration in uninfected rats and rats infected with Pseudomonas aeruginosa. - Omri, A (1994)
The pulmonary residence time of free and liposome-encapsulated tobramycin was studied with uninfected rats and rats infected with Pseudomonas aeruginosa. Chronic infection in lungs was established by intratracheal administration of 10(8) CFU of P. aeruginosa PA 508 prepared in agar beads. After 3 days, a single dose (300 micrograms) of free or liposome-encapsulated tobramycin was given intratracheally to both infected and uninfected rats. At various time intervals (0.25 to 16 h) after drug instillations, the remaining tobramycin was evaluated in blood, lungs, and kidneys by a microbiological assay. Intratracheal instillation of liposome-encapsulated tobramycin resulted in high and sustained levels of tobramycin in lungs of uninfected and infected rats over the 16-h period studied; however, the tobramycin levels were two times higher in uninfected rats. There was no tobramycin detected in the blood or kidneys from these animals. In contrast, the intratracheally instilled free tobramycin was cleared within 3 and 1 h from the lungs of uninfected and infected animals, respectively. These data suggest that the encapsulation of tobramycin in liposomes can result in a significant increase of its residence time within lungs. This study also shows that pulmonary infection was associated with a lowering of tobramycin levels in lungs.